“Imitating Bandits”: The Mimesis of Criminal Groups in Soviet Lithuania (1945–1957) - Indrišionis, Darius (Lietuvos istorijos studijos, 2019)
During the 1940s–1950s, the Supreme Court of the Lithuanian SSR solved 44 criminal cases of “banditry” (Article 59 part 3 of RSFSR Criminal Code of 1926) with some noticeable facts of mimesis: these bandits, during their raids, were trying to create an illusion to their victims that these raids were performed by Lithuanian partisans (freedom fighters) or by some Soviet oficials (militia officers, the “defenders of the People,” or Soviet army personnel). This article focuses on the mimesis of various criminal groups in Soviet Lithuania of the 1940s–1950s. The first issue to solve in this research is the problematic terminology used by the Soviets: the term bandit was oftenly used in Soviet ideological discourse: an attempt to intertwine anti-Soviet partisan operations (“political banditry,” according to Soviet terminology) and the activities of “simple criminals” (burglars, raiders, rapists, murderers – any of such organized groups were referred to as “criminal bandits” by Soviet terms) under a single dubious term – the banditry. An analysis of criminal raids performed by fake partisan (or fake Soviet) bandit groups showed that criminals were more often inclinded to appear as if they were Soviets rather than partisans (21 bandit group used the mimesis of partisans, and 27 bandit groups used the mimesis of Soviets, while there were also 4 bandit groups that used both roles: fake partisans during one raid and fake Soviets during another). This can be explained by the bandits’ avoidance of becoming the targets of partisan revenge or by a large number of various criminals that migrated to Soviet Lithuania from the eastern republics of the Soviet Union. It may also be explained in terms of simpler imitation: for these criminals, it was more difficult to imitate Lithuanian partisans than Soviet militia.The real widespread effect of this phenomenon cannot be easily revealed. As there several few different types of courts (Soviet military courts, the “People’s” courts) that could solve the criminal cases of various criminal bandits, it is not even possible to give a real number of all mimetic bandits that were active in Soviet Lithuania. Also, not every raid case was documented by the Soviet side; not every raid case was even reported to the Soviets. Sometimes, Lithuanian partisans used to catch and punish these criminals themselves – all these circumstances makes the task of stating the real number of bandit groups who used various mimesis techniques an unsolvable one.
Keywords: Lithuanian Soviet Socialist Republic; post-war period; Lithuanian freedom struggle; criminal banditry; RSFSR Criminal Code of 1926; Supreme Court of the Lithuanian SSR